Escape of mouse mastocytoma P815 after nearly complete rejection is due to antigen-loss variants rather than immunosuppression (The Rockefeller University Press, 1983)
Even though mastocytoma P815 often undergoes a nearly complete rejection in syngeneic mice, the tumor cells almost always escape to form progressive tumors. We found that this was not due to the establishment of an immunosuppressed state because genetically marked P815 cells, that were injected in mice where tumor escape was occurring, were readily rejected. An analysis of escaping tumor cell populations with anti-P815 cytolytic T lymphocyte (CTL) clones showed the presence of stable resistant variants. Using antigen-loss variants found in escaping populations or selected in vitro with CTL clones, we were able to define four different tumor-associated antigenic specificities, each recognized by a specific CTL clone. One of these specificities was absent from all escaping tumor cells and another had been lost by some of them.